The legally protected right of the crime of abandonment and acts of cruelty to domestic and wild vertebrate animals held in captivity (article 206 A) in the Peruvian Criminal Code - Franciskovic Ingunza, Beatriz (2021)
The purpose of this paper is to identify and analyze the legally protected right or interest of the crime of abandonment and acts of cruelty to animals governed by article 206 section A of the Peruvian Criminal Code. In order to better understand this, certain concepts must be clarified first, such as: what does the term animal mean, what animals are included, who is the perpetrator and who is the victim of this crime. This crime was introduced into our legal system only in 2016 with the passing of the Law on Animal Protection and Welfare. Overall, we conclude that article 206 A of the Criminal Code must refer to companion animals and not to all domestic vertebrates.